Expressiveness. A methodological approach (Itinera, 2022)
The debate on expressiveness is one of the most relevant in contemporary aesthetics. In fact, the possibility of an emotional linguistic expression referring to artistic objects or natural situations crosses a number of themes of classical and analytical aesthetics. The aim of this essay is therefore to enucleate what the presuppositions of a theory of expressiveness should be, starting from their historical genesis in the «expression theory» elaborated by Dewey. In particular, through the critical examination of two contemporary orientations on this issue – the Wollheim projectivist theory and the profile one by Kivy –, the aim is to bring attention to two indispensable aspects of a theory of expressiveness, which, although in need of revision, were already recognizable in the expression theory: a. a theory of intentionality and b. the dialectical consideration between Leib and Körper. In particular, the direction sketched at the end would suggest that it is this dialectical experience of the body that could be considered as the intentional condition for the existence and recognizability of expressive phenomena.